MEMORIES OF THE FREEDOM FIGHTERS: THE INDE X OF PE RSONAL NAMES OF THE 1944–1953 PARTISAN WAR PARTICIPANTS - Petrauskienė, Aistė (Acta Museologica Lithuanica, 2015)
This publication has been prepared alongside the increasing number of Romas Kaunietis books. Today the series of books Memories of the Freedom Fighters comprise 11 thick volumes. There are many dramatic stories about partisans, their liaisons and supporters and these books mention around 33,500 people and publish around 1,000 people’s memories. This consolidated index of personal names should facilitate the work of those who are looking for information. Much attention is paid to codenames, and a codename list of the partisan war participants is published here. R. Kaunietis, called the chronicler of the partisans, is a laureate of Felicija Botkevičienė’s language prize. His careful work is discussed in the publication. The publication also reviews the commemoration of the partisan war (Chapter I), because the freedom fighters spoke about the future. They hoped that not only their graves and monuments would remind people about the partisans’ war. Freedom fighters endeavoured to ensure that descriptions of historical events would remain until the Independence of Lithuania. R. Kaunietis, like the partisans, wanted to keep their memory alive. Therefore in 1966 he wrote his first memoirs of partisans, deportees and members of underground organisations (Chapter II). It is not surprising that members of the partisan war, their relatives and progeny, and promoters of history have been the ones who have taken most care to preserve the memory of the partisan war . The research on the partisan war participants’ codenames arose in 2010–2014, when the author of this publication communicated with partisan war participants. It is closely related to the persons index of the Memories of the Freedom Fighters series of books, so is published in this publication (Chapter III).